Noninvasive Measures of Liver Fibrosis and Severity of Liver Disease - Lucero, Catherine (Gastroenterol Hepatol (N Y), 2016)
Determining the degree of fibrosis is an important step in the assessment of disease severity in patients with chronic liver disease. Liver biopsy has been the gold standard for estimating the extent of inflammation and fibrosis, although the procedure has limitations such as sampling error and variability. Noninvasive testing has been shown to be equally predictive in ruling out fibrosis or ruling in advanced fibrosis. Serum biomarkers and imaging-based tests have more limited predictive ability when classifying intermediate stages, but these tools can help identify which patients should receive antiviral treatment sooner and require ongoing cancer surveillance without the need for biopsy. Using a combination of serum markers and imaging tests may also be helpful in providing functional assessment of portal hypertension in patients with chronic liver disease.